Overview of Student’s Mental Health with Broken Home Background - Halimah, Halimah; Darmayanti, Nefi (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
The purpose of this study was to determine the mental health of students from broken home backgrounds. The method used in this study was qualitative descriptive research with a total population of class VII A-C of 105 students and a sample of 6 students. The results of the study showed that disharmonious, unstable, messy family conditions (broken home) can cause the development of unhealthy personalities in children. The form of mental health in question includes aspects of emotion, responsibility and sociability of children. Students admitted that they had vented their emotions on objects around them and even experienced trauma due to physical violence when dealing with their mothers so that the students decided to work after school. In addition, students also felt depressed and considered a burden on the family so that every problem they faced only chose to keep to themselves so that it had a bad impact on their academics, so that serious handling was needed such as providing counseling guidance.